Resilience and gender-based violence: An interdisciplinary reflection on shaping stories of resilience from an institutional perspective - Potgieter, Annette; Johannisen, Jessica (Stellenbosch Theological Journal, 2023)
During the national lockdown in 2020, President Cyril Ramaphosa voiced concern about the ongoing problem of gender-based violence (GBV) in South Africa, calling it a pandemic alongside the COVID-19 pandemic. COVID-19 intensified the occurrence of gender-based violence within South African communities which consequently highlighted the need for awareness regarding this phenomenon. South Africa is a predominantly Christian culture, yet the actions of community members seem to be defined by patriarchal cultures. There is therefore a need to rethink how we address social issues, especially GBV. This article aims at providing an interdisciplinary reflection on shaping stories of resilience relating to gender-based violence from the perspectives of both theology and social work at Hugenote Kollege.